Political Accountability During Crises: Evidence from 40 Years of Financial Policies - Orkun Saka; Yuemei Ji; Clement Minaudier (CESifo GmbH, 2024)
We show that politicians facing a binding term limit are more likely to engage in financial de-liberalisation than those facing re-election, but only in the wake of a financial crisis. In particular, they implement policies that tend to favour incumbent financial institutions over the general population, such as increasing barriers to entry in the banking sector. We rationalise this behaviour with a theory of political accountability in which crises generate two opposite effects: they increase the salience of financial policies to voters but also create a window of opportunity for politicians captured by the financial industry to push potentially harmful reforms. In line with the implications of our model, we show that revolving doors between the government and the financial sector play a key role in encouraging bank-friendly policies after crises.
Keywords: D72; D78; G01; P11; P16; 330; financial crises; political accountability; democracies; term-limits; special-interest groups